2013
DOI: 10.4103/0019-5154.117293
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing practices of topical corticosteroids in the outpatient dermatology department of a rural tertiary care teaching hospital

Abstract: Background:Inappropriate or excessive use of topical corticosteroids can lead to cutaneous and systemic adverse effects which occur more commonly with the use of very potent steroids. Monitoring and analysis of the prescription practices of topical steroids can help to achieve rational prescription of these drugs.Aim:The present study was carried out to study and analyze the pattern of prescribing topical corticosteroids among outpatients attending the dermatology clinic in a rural tertiary care and teaching h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“… 5 Topical corticosteroids can cause cutaneous side effects (atrophy, striae, telangiectasia, hypo-pigmentation, acne, rosacea, perioral dermatitis, and hypertrichosis), as well as systemic side effects (cataracts, hyperglycemia, and hypothalamic-pituitary-adrenal suppression). 6 While their prescribing patterns have been studied, 7 - 10 the knowledge based upon which these PCPs choose a TC has not been identified. Our study aims to assess the current knowledge, attitudes, and practices of PCPs toward TCs in Riyadh, Kingdom of Saudi Arabia (KSA).…”
mentioning
confidence: 99%
“… 5 Topical corticosteroids can cause cutaneous side effects (atrophy, striae, telangiectasia, hypo-pigmentation, acne, rosacea, perioral dermatitis, and hypertrichosis), as well as systemic side effects (cataracts, hyperglycemia, and hypothalamic-pituitary-adrenal suppression). 6 While their prescribing patterns have been studied, 7 - 10 the knowledge based upon which these PCPs choose a TC has not been identified. Our study aims to assess the current knowledge, attitudes, and practices of PCPs toward TCs in Riyadh, Kingdom of Saudi Arabia (KSA).…”
mentioning
confidence: 99%
“…A study conducted at a rural tertiary care hospital in India concluded that 28% of prescription had Topical steroids, out of which 98% were very potent corticosteroids; and in 85% of cases, the basis of prescribing these could not be established. 16 Widespread use of topical steroids in off label manner is supported by the evidence that these medications are perceived to be safe by the prescribing physicians as they do not cause systemic steroid toxicity. However topical adverse effects of these medications are often ignored.…”
Section: International Journal Of Contemporary Medical Researchmentioning
confidence: 99%
“…Also, it has been sometime observed that even trained physicians and dermatologists are prescribing either the wrong strength of TC or for the wrong indication. [ 8 ] Regular continuing medical education and workshops to create awareness regarding this important issue will go a long way to ensure rational use of TCs. Along with this, there is need to sensitize patients, the actual user, about the adverse effects of TC abuse on face.…”
Section: Regulatory Challenges For Topical Corticosteroids In Indiamentioning
confidence: 99%
“…[ 4 5 ] However, the more serious concern is its inappropriate use in symptomatic treatment for varied dermatological disorders like acne, primary bacterial and fungal infections, undiagnosed skin rash and as fairness cream by non-registered practitioners or on the advice of pharmacist at chemist shops. [ 6 7 8 ] These people are not qualified and competent to treat dermatological disorders and prescribe topical steroids which often provide quick symptomatic relief without treating the underlying pathology of the disease. Ironically, the Indian market is flooded with several fixed-dose combinations (FDCs) of corticosteroids with antibacterial and fungal agents, which in no way can be considered as scientific and rational.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation